Persepsi Masyarakat Terhadap Rencana Pembangunan Pembangkit Listrik Tenaga Panas Bumi (PLTP) Di Desa Idamdehe, Kabupaten Halmahera Barat, Provinsi Maluku Utara - Brian L. Djumaty; Nina Putri Hayam Dey (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2018)
Development is a process to accelerate economic growth, reduce gaps and eradicate poverty.Besides that development is also a multidimensional process of important changes in socialstructure, the attitude of the people and national institutions. Therefore, in this study, theauthors will examine the public perception of the planned development of Geothermal PowerPlant (PLTP) in Idamdehe Village, District Jailolo, West Halmahera, North Maluku Province.The reason the author took this topic because the village will be built PLTP. The researchmethodology used is qualitative descriptive. From the results of the research shows that thedevelopment plan of PTLP in Idamdehe village has been socialized since 2011-2013. From theeffects of the socialization of the community get information about PTLP. There are threegroups of perceptions about the PLTP development plan that is Agree, Disagree and Doubtful.